Natural law theory - Angier, Tom 1970- (Cambridge elements, 2021)
In Section 1, I outline the history of natural law theory, covering Plato, Aristotle, the Stoics and Aquinas. In Section 2, I explore two alternative traditions of natural law, and explain why these constitute rivals to the Aristotelian tradition. In Section 3, I go on to elaborate a via negativa along which natural law norms can be discovered. On this basis, I unpack what I call three 'experiments in being', each of which illustrates the cogency of this method. In Section 4, I investigate and rebut two seminal challenges to natural law methodology, namely, the fact/value distinction in metaethics and Darwinian evolutionary biology. In Section 5, I then outline and criticise the 'new' natural law theory, which is an attempt to revise natural law thought in light of the two challenges above. I conclude, in Section 6, with a summary and some reflections on the prospects for natural law theory